990. NICOTIANA INGULBA: Solanaceae. (13th August 2021) - Chase, Mark W.; Dodsworth, Steven; Christenhusz, Maarten J. M.
Summary: Nicotiana ingulba is returned to species level here. It is illustrated from plants cultivated at the Royal Botanic Gardens, Kew, which were grown from seeds collected in the Uluru‐Kata Tjuta National Park in the Northern Territory, Australia. Its taxonomic history, ecology, cytology, etymology and cultivation are discussed.